A deadly dedication - Loudon, Margaret (Loudon, Margaret. Open book mysteries., 2023)
When the owner of Upper Chumley-on-Stokes's proposed first high-end gourmet shop is poisoned, American novelist and bookstore owner Penelope Parish is faced with a long list of suspects that makes this page-turning mystery her toughest yet.